Orbital autoimmune inflammatory disorders - Protein regional variability might explain specific lesion location. (January 2017) - Clarke, Margo S.; Plouznikoff, Alexandre; Deschenes, Jean
Abstract: In ophthalmology, inflammatory diseases target different highly specific regions within the small confine of the orbit. Some entities even prefer a particular location or depth within the same tissue (ex. anterior, intermediate or posterior uveitides, chorioretinitides with unique topographic presentations). Though the location of a lesion strongly influences and helps us in our differential diagnosis, we still don't understand why specific anatomic sites are susceptible to a disease while other areas are spared. We postulate that regional variability in tissue protein expression can sway the immune system's capacity to trigger an autoimmune response. In addition to this site-specific quantitative and qualitative variability in potential antigen expression, we believe that other proteins implicated in the immune cascade, as well as geographic areas of relative resistance, tolerance and susceptibility, may be unequally distributed within the orbit. To illustrate our hypotheses, we review three major types of ocular myositis and describe how the extraocular muscles different embryologic origins and protein disparities might explain the fundamental clinical differences between these orbital inflammatory diseases. We hope that future differential genomics, proteinomics, epigenomics and analysis of RNA species of affected tissues, compared to their non-affected, yet microscopically similar, counterparts, will help us understand why diseases occur where they do. Hopefully, understanding these immune triggers will pave the way to new treatment options for ocular inflammatory diseases and for other auto-inflammatory conditions with a marked predilection for any given site.